Pharmacological inhibition of sphingolipid synthesis reduces ferroptosis by stimulating the HIF-1 pathway - Liu, Yang; He, Libo; Liu, Binghua; Ying, Yuling; Xu, Junling; Yu, Meng; Dang, Jinye; Liu, Ke (iScience, 2022)
Ferroptosis is crucial to the pathology of many neurological diseases. Here, we found pre-treatment with myriocin, an inhibitor of de novo synthesis of sphingolipid, significantly decreased the erastin- or glutamate-induced ferroptosis of HT22 cells without requiring the recovery of intracellular glutathione. The transcriptome analysis of HT22 cells treated with or without myriocin identified the hypoxia-inducible factor 1 (HIF-1) pathway as a prime and novel drug target. Further study validated that HIF1α was required for the cytoprotective effects of myriocin. Myriocin treatment promoted the expression of HIF-1 pathway effectors including PDK1 and BNIP3 and altered the intracellular levels of glucose metabolites. Additionally, myriocin treatment stabilized HIF1α protein by decreasing its ubiquitination and proteasomal degradation. Similar effects of myriocin on HIF1α stabilization were also found in other mammalian cell lines indicating this is a common mechanism for the cytoprotective role of myriocin. [Display omitted] •Inhibiting sphingolipid synthesis by myriocin reduces the ferroptosis•Myriocin activates the HIF-1 pathway•The effects of myriocin on ferroptosis require HIF1α•Myriocin stabilizes HIF1α protein by reducing its ubiquitination Biological sciences; Neuroscience; Cellular neuroscience; Cell biology